Power in Sensemaking Processes - Schildt, Henri; Mantere, Saku; Cornelissen, Joep (Organization studies, 2020)
This article examines the effects of power on sensemaking processes, bridging two major, yet traditionally separate, literatures in organization studies. Dividing power into its systemic and episodic forms, we elaborate how power shapes not only the content of sensemaking, but also the form of sensemaking processes. We explicate the distinct ways in which power works in four archetypal sensemaking processes: automatic (preconscious and committed), improvisational (preconscious and provisional), algorithmic (conscious and committed) and reflective (conscious and provisional). These ideal-type processes help us theorize how influences related to systemic and episodic power induce more or less conscious and provisional forms of sensemaking. This refined understanding of sensemaking processes enables further explication of episodic power into distinctive kinds of sensegiving and sensebreaking activities.